Multi-Technology Positioning - Nurmi, Jari; Lohan, Elena-Simona; Wymeersch, Henk; Seco-Granados, Gonzalo; Nykänen, Ossi (Springer International Publishing : Imprint: Springer, 2017)
This book provides an overview of positioning technologies, applications and services in a format accessible to a wide variety of readers. Readers who have always wanted to understand how satellite-based positioning, wireless network positioning, inertial navigation, and their combinations work will find great value in this book. Readers will also learn about the advantages and disadvantages of different positioning methods, their limitations and challenges. Cognitive positioning, adding the brain to determine which technologies to use at device runtime, is introduced as well. Coverage also includes the use of position information for Location Based Services (LBS), as well as context-aware positioning services, designed for better user experience. • Brings understanding of positioning technology to readers from a variety of disciplines • Reviews multiple techniques, providing insight on the pros, cons and challenges related to each • Designedto be a tutorial on basic principles, avoiding unnecessary detail • Offers lessons learned from a cross-sector international network, from both academic and industrial perspective and from a multi-cultural view.